Os planos diretores sob a óptica do desenvolvimento sustentável e cidade saudável: o estudo nos municípios de Ituiutaba e Uberlândia - MG - Gontijo, Carlos Eduardo de Oliveira (2017)
This research addresses the theme related to the planning of municipalities in the development of public policies for the protection of the environment and a healthy life. It was tried to answer if there is adequacy of the forecasts of the Master Plans of the Municipalities of Ituiutaba and of Uberlândia both of the State of Minas Gerais under the perspective of the environmental sustainability and of a Healthy City. Thus, as a general objective, the objective was to develop criteria to assess the adequacy of the forecasts of a Master Plan from the perspective of environmental sustainability and a Healthy City, and then to analyze the degree of adequacy related to the Master Plan of the Municipalities of Ituiutaba and Of Uberlândia. To accomplish this broader objective, the specific objectives of: a) analyzing the concepts of Sustainable Development and Healthy City; B) identify criteria for checking environmental sustainability and a Healthy City; C) show the minimum legal content of a Master Plan under the focus of Sustainable Development and a Healthy City; D) to evaluate the adequacy of the forecasts of the Master Plan of the Municipalities of Ituiutaba and Uberlândia considering the criteria developed. The following methodological procedures were adopted: theoretical research, documentary and case research. A theoretical revision was made from the consultation in books, periodicals articles, specialized magazines, documents, monographs, dissertations theses and sites making use of primary and secondary sources. As for the documentary research, consultations were carried out on official websites such as the Brazilian Institute of Geography (IBGE), the World Health Organization (WHO), the United Nations (UN), the Municipalities of Ituiutaba and Uberlândia. After the elaboration of the checking criteria and applied to assess the Management Plans of the selected Municipalities, it is concluded that there is a need to review them, considering specific gaps in this research and the following structural failures present in both Master Plans: a) there are guidelines, objectives And actions in the Executive Plans, but without specifying any goal, besides, as a rule, there are no deadlines in the Master Plans to achieve them; B) there is no systematic identification of the need for training according to objectives and goals to be achieved by the Executive Plans; C) the absence of goals and targets in the Master Plans impairs the effectiveness of the system of monitoring the established guidelines. Finally, it was inferred by the need for revision of the Executive Plans, given that such structural failures may compromise the promotion of Municipalities with a focus on Sustainable Development and a Healthy City.